Effects of additional plyometric training on the jump performance of elite male handball players: a systematic review - Jakši´c, D.; Mari¡ci´c, S.; Maksimovi´c, N.; Bianco, A.; Sekuli´c, D.; Foreti´c, N.; Drid, P. (International Journal of Environmental Research and Public Health, 2023)
Handball is one of the most popular team sports around the world that has become physically very demanding, related to both competitions and daily training sessions. Optimal training programs are necessary to improve performance, especially when taking into account the frequency of jump shots (vertical jumps) and handball feints (changes of directions) during daily training. The main objective of the present study is to review the available literature systematically, and to determine what are the effects of additional plyometric training on handball players` vertical jump abilities. According to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis, six studies were selected after a systematic search through four digital databases: Web of Science, PubMed, Scopus, and ScienceDirect. The available scientific articles show that plyometric training alone or in combination with standard handball training, lasting at least six weeks, and including two training sessions per week, contributes to improving the performance of elite- or national-level handball players. Plyometric training is recommended to improve performance, as well as to maintain explosive strength parameters during the season.